1974
DOI: 10.2307/1942450
|View full text |Cite
|
Sign up to set email alerts
|

Stability in Relation to Nutrient Enrichment in Arthropod Consumers of Old‐Field Successional Ecosystems

Abstract: Two adjacent, abandoned hayfields in central New York State were subjected to nutrient enrichment perturbation by means of a single application of 10-10-10 N, P, K fertilizer early in the growing season of 1970. Aboveground arthropod herbivores and carnivores were monitored with respect to net productivity (dB/dt) and diversity for one growing season (1970) in the younger field (6 yr old), and for two growing seasons (1970 and 1971) in the older field (17 and 18 yr old). Sampling of arthropods was done with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
2
1

Year Published

1983
1983
2019
2019

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(69 citation statements)
references
References 56 publications
4
62
2
1
Order By: Relevance
“…Herbivore and detritivore biomass also increased in some fertilised blocks, but this effect was weak and variable (Table 2), consistent with a related study that showed smaller individuals dominate the response to nutrient enrichment (Gruner, 2004b). Responses of community species richness or diversity in other studies have been more variable and equivocal than abundances (Hurd & Wolf, 1974;Kirchner, 1977;Sedlacek et al, 1988;Haddad et al, 2000). Discrepancies in the qualitative responses of diversity across systems may be biologically based and system specific, or might vary according to differences in spatial scale (Whittaker & Heegaard, 2003), trophic or taxonomic focus (Haddad et al, 2000), diversity metric or standardisations employed (McCabe & Gotelli, 2000), or experimental time frame (Haddad et al, 2000).…”
Section: Community Responses To Fertilisationsupporting
confidence: 86%
“…Herbivore and detritivore biomass also increased in some fertilised blocks, but this effect was weak and variable (Table 2), consistent with a related study that showed smaller individuals dominate the response to nutrient enrichment (Gruner, 2004b). Responses of community species richness or diversity in other studies have been more variable and equivocal than abundances (Hurd & Wolf, 1974;Kirchner, 1977;Sedlacek et al, 1988;Haddad et al, 2000). Discrepancies in the qualitative responses of diversity across systems may be biologically based and system specific, or might vary according to differences in spatial scale (Whittaker & Heegaard, 2003), trophic or taxonomic focus (Haddad et al, 2000), diversity metric or standardisations employed (McCabe & Gotelli, 2000), or experimental time frame (Haddad et al, 2000).…”
Section: Community Responses To Fertilisationsupporting
confidence: 86%
“…However, the estimates of species richness from individual-based rarefaction did not increase with fertilization for any trophic group. Numerous studies have examined the diversity of herbivorous or other arthropods in response to fertilization, but generalizations have been elusive (e.g., Hurd and Wolf 1974;Kirchner 1977;Kajak 1981;Vince et al 1981;Prestidge 1982;Strauss 1987;Sedlacek et al 1988;Siemann 1998;Haddad et al 2000). However, several of these studies observed higher abundance of sap-sucking Auchenorryncha and other herbivorous groups, but decreasing evenness and diversity as a small number of species emerged as dominant (Prestidge 1982;Sedlacek et al 1988;Haddad et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, generalist predators like these mantid nymphs exert different effects on the plant community than would a specialist predator attacking only one or a few prey items. Another effect of enhanced primary production on consumers may be increased fecundity, which would show up as higher abundance and secondary productivity the following season (Hurd and Wolf 1974). In any case, that mantids can exert strong direct and indirect effects on herbivorous arthropods has been documented by Eisenberg (1984b, 1990a) for T. sinensis, and by Mook and Davies (1966) and Hurd (1991, 1994) for another temperate mantid, Mantis religiosa.…”
Section: Cascading Trophic Effectsmentioning
confidence: 95%